The Responses of Rat Intestinal Brush Border and Cytosol Peptide Hydrolase Activities to Variation in Dietary Protein Content DIETARY REGULATION OF INTESTINAL PEPTIDE HYDROLASES - J. Alex Nicholson; Denis M. McCarthy; Young S. Kim (The Journal of Clinical Investigation, 1974)
The effects of variation in dietary protein content on small intestinal brush border and cytosol peptide hydrolase activities have been investigated. One group of rats was fed a high protein diet (55% casein) and another group was fed a low protein diet (10% casein). After 1 wk, brush border peptide hydrolase activity (L-leucyl-β-naphthylamide as substrate) and cytosol peptide hydrolase activity (L-prolyl-L-leucine as substrate) were determined in mucosae taken from the proximal, middle, and distal small intestine. As judged by several parameters, brush border peptide hydrolase activity was significantly greater in rats fed the high protein diet when data for corresponding segments were compared. In contrast, no significant difference was seen in cytosol peptide hydrolase activity. In a second study, brush border and cytosol peptide hydrolase activities were determined in the proximal intestine by utilizing an additional three peptide substrates: L-leucyl-L-alanine, L-phenylalanylglycine, and glycyl-L-phenylalanine. Sucrase, maltase, and alkaline phosphatase activities were also determined. As before, brush border peptide hydrolase activities were significantly greater in rats fed the high protein diet. However, activities of the nonproteolytic brush border enzymes did not vary significantly with diet. In contrast to the results obtained with L-prolyl-L-leucine as substrate for the cytosol enzymes, cytosol activity against the three additional peptide substrates was greater in rats fed the high protein diet. It is suggested that the brush border peptide hydrolase response to variation in dietary protein content represents a functional adaptation analogous to the regulation of intestinal disaccharidases by dietary carbohydrates. The implication of the differential responses of the cytosol peptide hydrolases is uncertain, since little is known of the functional role of these nonorgan-specific enzymes.